Enhancing maternal role achievement and breastfeeding success through health belief model intervention - Nurus Safaah; Esti Yunitasari; Budi Prasetyo; Mira Triharini; Pipit Feriani (PAGEPress Publications, 2024)
Breastfeeding is a critical component of maternal and infant health. The study, conducted from April to June 2023, aimed to evaluate the impact of the mother's role achievement module on breastfeeding practices among postpartum mothers in Indonesia. Sixty participants were divided into intervention and control groups in a quasi-experimental setup. The intervention group showed remarkable improvements: a 25% increase in breastfeeding frequency, a 15% weight gain, a 30% enhancement in proper breastfeeding technique, a 20% improvement in breast care practices, and a 25% boost in nutritional intake compared to the control group. Conversely, the control group showed a reduced breastfeeding frequency by approximately 20%, a 10% decrease in weight, a 35% inadequacy in breastfeeding technique, varied breast care practices, and insufficient nutritional intake, showcasing the disparity between the groups. Statistical analyses, including Mann-Whitney and Chi-Square tests, confirmed these significant differences, emphasizing the module's substantial impact on breastfeeding success among postpartum mothers. In conclusion, tailored interventions based on the Health Belief Model play a pivotal role in enhancing maternal and infant health outcomes in Indonesia. This study recommends integrating similar approaches into healthcare policies to bolster breastfeeding practices among postpartum mothers, potentially improving overall maternal and infant health in the region.